Development of a 2∼4 K closed-cycle JT cryocooler for space application. Issue 1 (1st May 2022) - Pan, Xiaoshan; Liu, Shaoshuai; Wu, Yinong; Jiang, Zhenhua; Ding, Lei
Abstract: Cryogenic system proving cooling capacity at liquid helium temperatures is one of the key technologies for space exploration missions. A closed-cycle Joule-Thomson cryocooler capacity of providing different cooling powers at 2∼4 K is developed in our lab. The cryocooler is precooled by a two-stage thermal coupled pulse-tube cryocooler with active phase shifter and driven by multi-stage valved linear compressors. The lowest temperature about 2.5 K and more than 50 mW at about 4.0 K can be obtained by adapting the suited charging pressures. The two-stage pulse tube cryocooler can provide pre-cooling capacity at 17 K and 76 K, respectively with an input power of about 350 W. A large pressure ratio of about 26 and a mass flow rate of 6.7 mg/s can be provide by the multi-stage valved linear compressors with a charge pressure of 0.6 MPa and a total electrical power of less than 110 W. The cooling-down time for the cryocooler from room temperature to about 4 K is less than 10 hours. The cooling system can provide a required cryogenic environment for future space applications.